2022
DOI: 10.3390/ma15020584
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbon Sorbent Quantity on Breakthrough Time in Absorbent Filters for Antismog Half Mask Application

Abstract: In this article, we present polymer non-woven fabrics with the addition of carbon sorbents being tested to estimate the breakthrough time and efficient protection against vapors present in smog. For this purpose, three substances were selected, which constitute an inhalation hazard and are smog components: cyclohexane, toluene, and sulfur dioxide. It was demonstrated that an increased quantity of carbon sorbent in polymeric filters significantly prolongs the breakthrough time. However, high sorbent quantities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In the case of half-mask 1, the first increment in the downstream concentration of sulfur dioxide vapors did not occur until 5 h of the experiment. These results are consistent with the study by Brochocka et al [ 9 ], who reported that a filtering material incorporating activated carbon particles offered protection against sulfur dioxide for 6 h.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In the case of half-mask 1, the first increment in the downstream concentration of sulfur dioxide vapors did not occur until 5 h of the experiment. These results are consistent with the study by Brochocka et al [ 9 ], who reported that a filtering material incorporating activated carbon particles offered protection against sulfur dioxide for 6 h.…”
Section: Resultssupporting
confidence: 93%
“…z o.o., Warsaw, Poland) to which AG Pleisch 30180 PL MC 12 × 20 CBRN carbon sorbent (PLEISCH, Bäretswil, Switzerland) was added. It has been shown that the comminution of carbon sorbent in a planetary mill does not adversely affect its textural properties [ 9 ]. In addition, three commercially available FFP2 filtering half-masks with a carbon sorbent were included in the study for the purpose of comparing protection times and morphological structures.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations